Molecular identification and phylogenetic analysis of confusing Tetrastigma species based on DNA barcoding and chloroplast genome - Li, Xianjing; Zhang, Yue; Song, Meifang; Xu, Niaojiao; Qu, Lu; Li, Haitao; Wang, Yunqiang; Duan, Baozhong; Zhang, Zhonglian (Frontiers in Pharmacology, 2025)
BackgroundTetrastigma plants are widely utilized in traditional medicine (such as Tetrastigma. obtectum and Tetrastigma. serrulatum, two important commonly medicinal plants), primarily for their properties in promoting blood circulation, strengthening bones and tendons, and so on. However, the high diversity of species differentiation poses a challenge in accurately identifying the various Tetrastigma species without specialized taxonomic knowledge.Materials and methodsTo screen the candidate barcode sequences of Tetrastigma species, we first report the complete chloroplasts (CP) genomes of T. obtectum and T. serrulatum obtained via high throughput Illumina sequencing and compare them with fourteen previously sequenced species. Furthermore, we collected fresh leaf samples from T. obtectum and T. serrulatum (totally 37 samples) and evaluated the discriminatory efficacy of the nuclear DNA Internal Transcribed Spacer 2 (ITS2) fragment through comparative analysis of sequence variations and secondary structures. Finally, to analyze the phylogenetic position of Tetrastigma species, we constructed a Maximum Likelihood (ML) phylogenetic tree using CP genome sequences of 46 species from seven genera within the Vitaceae family.Results and discussionThe CP genomes of Tetrastigma exhibited a typical circular tetramerous structure, including a large single-copy region (LSC) (87,381–88,979 bp), a small single-copy region (SSC) (18,649–19,339 bp), and a pair of inverted repeats (IRa and IRb) (26,288–26,934 bp). The guanine-cytosine content of the CP genomes is 37.35%–37.62%. The codon usage shows a significant preference for end with A/T. Then, the results of nucleotide diversity analysis showed that ten polymorphic hotspots (psbM-trnD-GUC, ndhF-rpl32, trnS-GCU-trnG-UCC, ycf1, rpl32-trnL-UAG, trnS-UGA-psbZ, psbE-petL, matK-rps16, rpl16, and rpl22) could be the candidate DNA marker suitable for Tetrastigma species. Furthermore, our results demonstrate that the ITS2 sequence could effectively discriminate T. obtectum and T. serrulatum, whereas the secondary structure cannot, proving that ITS2 can be used as an efficient barcode fragment to accurately identify the two species. The aim of this study was not only to determine the identification efficiency of the CP genome and ITS2 for T. obtectum and T. serrulatum but also to clarify the phylogenetic relationship and screen the candidate DNA marker suitable for Tetrastigma species, provide valuable data support for further accurate identification of the Tetrastigma genus.